Analisis Pengaruh Pandemi Covid 19 Terhadap Emiten Properti: Studi Kasus Emiten Properti Dalam LQ-45 - Hanifah Qianis Sari; Abdul Rahman (CV ODIS, 2021)
The covid 19 pandemic is a disaster that impacts all sectors especially the economic sector in Indonesia. Indonesia’s economics whose growth significantly should decrease again because of the corona outbreak. Property field which is focused on occupancy, residential, mall, apartment, etc should willing that income decreased in 2020. Social distance policy makes the public minimize to interacts. Even more, also many companies should out of business, and causing the unemployment rate to go up so that the public prefers to save money in pandemic which is an uncertain end. The impact can be seen from the company’s financial statement, especially in revenue growth also net income growth. Both facts can give information about product sales and profit of the company in a certain period. Both facts also can help the company to decide on sales of company products so that company will get maximum profit and customer loyalty.